2018 European YAC (M18,W18) Beach Handball Championships - Qualitative Analysis - Zapardiel Cortés, J. C. (EHF, 2018)
Beach handball is a sport that has acquired a great global recognition and, as an example, it is already participating in the Youth Olympic Games. The aim of this study was to make a quantitative and qualitative analysis of the European Championships of national teams held in Ulcinj between June 29 to July 1, 2017. To carry out this analysis, a comparison of different specific beach handball skills of this championship was made. To do this, the volunteers trained to collect data gathered information from 112 matches in situ. The data were statistically analyzed and the results were presented. Among the most interesting conclusions were: 1-point shots have increased considerably; throws with the lowest percentage of effectiveness are the goalkeeper`s; the inflight shot is the throw with the highest percentage of effectiveness; there are no differences between men and women when the percentage of goals is compared regarding the throw type.